2014
DOI: 10.1039/c3sm51393a
|View full text |Cite
|
Sign up to set email alerts
|

Structural and dynamical properties of reconstituted myelin sheaths in the presence of myelin proteins MBP and P2 studied by neutron scattering

Abstract: The myelin sheath is a tightly packed, multilayered membrane structure wrapped around selected nerve axons in the central and the peripheral nervous system. Because of its electrical insulation of the axons, which allows fast, saltatory nerve impulse conduction, myelin is crucial for the proper functioning of the vertebrate nervous system. A subset of myelin-specific proteins is well-defined, but their influence on membrane dynamics, i.e. myelin stability, has not yet been explored in detail. We investigated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
72
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(80 citation statements)
references
References 55 publications
8
72
0
Order By: Relevance
“…P2 is known to stack lipid bilayers together [7,11] and stabilize the membrane structure [12]. Previous neutron scattering studies have shown that P2 bound to myelinmimicking vesicles made either of 1,2-dimyristoyl-snglycero-3-phosphatidic acid (DMPA) or of a binary mixture of 1,2-dioleoyl-sn-glycero-3-phospho-L-serine (DOPS) and 1,2-dioleoyl-sn-glycero-3-phosphocholine (DOPC), respectively, reduces the lipid dynamics [13].…”
Section: Introductionmentioning
confidence: 99%
“…P2 is known to stack lipid bilayers together [7,11] and stabilize the membrane structure [12]. Previous neutron scattering studies have shown that P2 bound to myelinmimicking vesicles made either of 1,2-dimyristoyl-snglycero-3-phosphatidic acid (DMPA) or of a binary mixture of 1,2-dioleoyl-sn-glycero-3-phospho-L-serine (DOPS) and 1,2-dioleoyl-sn-glycero-3-phosphocholine (DOPC), respectively, reduces the lipid dynamics [13].…”
Section: Introductionmentioning
confidence: 99%
“…Secondly in the case where data were taken at different instrumental resolutions, each data set is fitted independently giving sometimes rise to different diffusion coefficients which in contrary should be parameters characterizing unambiguously the sample. In contrary, it has been shown in the case of lipids [7,8] that a fitting approach using models to describe existing motions a Corresponding author: martinezn@ill.fr from the beginning on allows a comprehensive and more accurate description of the system, which has dynamics spanning several orders of magnitude. The method was also applied to more complex systems such as neural tissue [9].…”
Section: Introductionmentioning
confidence: 99%
“…The second model implemented is destined to analyse data on lipids that consists of an elastic term, two components describing diffusion in a sphere of different radii [14], a third component describing jump-diffusion among two equivalent sites [6], and a large fourth component. Details on this model can be found in [7,8]. More models are foreseen to be implemented into the program within the next future.…”
Section: Available Functionsmentioning
confidence: 99%
“…), which can be investigated from microscale down to nanoscale, beyond the known averaged structures seen at larger scales. Moreover, in the case of myelin, there is great interest around the study of its structural fluctuations, and their relation to myelin proteins [8]. In this context, this new approach can provide unique information on the damage and degeneration of the myelin sheath, like demyelization.…”
Section: Introductionmentioning
confidence: 99%
“…It has a periodic multi-lamellar structure, whose unit is made up of the repetition of four layers: cytoplasmic apposition of Schwann cells (cyt), lipidic membrane (lpg) extracellular apposition of Schwann cells (ext) and another lipidic membrane (lpg). The available information about the myelin layers has been extracted from measurements performed by space averaged laboratory X-Ray Diffraction (XRD) [3][4][5][6], electron microscopy (EM) [6,7] and neutron diffraction [8].…”
Section: Introductionmentioning
confidence: 99%